Implementasi Kebijakan Pemberdayaan Aparatur Sipil Negara (ASN) Pada Dinas Sosial, Pemberdayaan Perempuan Dan Perlindungan Anak Kabupaten Sekadau - Petronela Eli; Yulius Yohanes; Herlan Herlan (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
The purpose of this research is to describe and analyze the implementation of Human Resources empowerment policies in the Office of Social Affairs, Women's Empowerment and Child Protection of Sekadau Regency and find out the factors that influence the empowerment of State Civil Apparatus within the Office of Social Affairs, Women's Empowerment and Child Protection of Sekadau Regency. The type of research is descriptive qualitative, namely aims to describe what is currently happening. In it there are efforts to describe, record, analyze and interpret the conditions that are currently occurring. The results showed that communication in the implementation of employee apparatus empowerment policies at the Sekadau Regency Office of Social Affairs, Women's Empowerment and Child Protection is the giving of trust by the leadership in granting authority to subordinates is always used as a basis for carrying out tasks within the agency so that employees with their obligations submit accountability in accordance with the orientation of the program that has been determined in the job description. In addition to the authority given by the leadership is clear according to the predetermined mechanism, the provision of support by the leadership of the staff feels motivated because of the attention given by the superiors so that the expected performance can be achieved. Resources seen from the ability of the State Civil Apparatus at the Sekadau Regency Office of Social Affairs, Women's Empowerment and Child Protection are classified as low. This is due to various factors, such as educational background, lack of authority, creativity and accuracy in employee placement. Disposition seen from an adequate number of employees does not guarantee the smooth running of services aimed at the community if these employees do not understand the substance of their duties properly. Therefore, it is necessary to have a clear and firm understanding of each task and function of each state employee in carrying out their duties, so that the employee can be empowered to provide the best service to the community. Bureaucratic structure in the Office of Social Affairs, Women's Empowerment and Child Protection of Sekadau Regency, namely the delegation of authority, is a form of concern or to complete a task responsibly. Delegation of authority must be based on needs by referring to the needs of each section in the agency.